ATTEMPT OF OVERCOMING SECONDARY INEFFECTIVENESS OF INFLIXIMAB IN A PATIENT WITH ANKYLOSING SPONDYLITIS USING PLASMAPHERESIS (A CASE REPORT) - Oksana Alekseyevna Rumyantseva; A G Bochkova; S K Soloviev; Sh F Erdes (Научно-практическая ревматология)
The article focuses on the problem of secondary ineffectiveness of tumor necrosis factor α infliximab (INF) and describes an attempt of using plasmapheresis (PF) to eliminate this problem in a patient with ankylosing spondylitis who had received INF treatment at a dose of 5 mg/kg for a long time (over 4 years). After PF, the IFF therapy ensured a long-term clinical and laboratory improvement of patient's condition. One can assume that PF made it possible to overcome secondary ineffectiveness of INF and can be used in some patients in cases when INF cannot be replaced with another TNFα inhibitor.